THE EFFECT OF A PROBLEM-BASED LEARNING MODEL ON STUDENTS' CRITICAL THINKING SKILLS IN PHYSICAL FITNESS GYMNASTICS MATERIAL AT SMP NEGERI 1 LAWE SIGALA-GALA - Hendra Putra; Fakhrur Rizal; Afrizal (RADJA PUBLIKA, 2025)
This study aimed to determine the effect of the Problem-Based Learning (PBL) model on students' critical thinking skills within the context of Physical Fitness Gymnastics, a component of Physical Education (PE). Employing a quasi-experimental design with a one-group pretest-posttest approach, the research was conducted with 30 eighth-grade students from SMP Negeri 1 Lawe Sigala-Gala, selected via total sampling. The intervention consisted of a series of lessons on the